2015
DOI: 10.1007/s00586-015-4263-9
|View full text |Cite
|
Sign up to set email alerts
|

Head repositioning accuracy in patients with neck pain and asymptomatic subjects: concurrent validity, influence of motion speed, motion direction and target distance

Abstract: The assessment of proprioceptive performance in healthy and NP subjects allowed the validation of the HRT. The HRT is a simple, not expensive and fast test, easily implementable in daily practice to assess and monitor treatment and evolution of proprioceptive cervical deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…In eight studies, a neutral task [27, 30, 42, 4749, 62, 64] including variables of absolute error [42, 48, 49, 62], constant error [30, 42], variable global error [30, 42], root mean square error [30], and maximal overshoot [49] was reported. In two studies, a mid-range task reporting on absolute [43, 69], constant, and variable global error was reported, and in three papers [48, 64, 65], no specification of the error measurement parameter was reported. All nine studies showed smaller joint positioning error for the healthy controls compared with the neck pain groups; the difference was statistically significant in five studies [27, 34, 47, 64].…”
Section: Resultsmentioning
confidence: 99%
“…In eight studies, a neutral task [27, 30, 42, 4749, 62, 64] including variables of absolute error [42, 48, 49, 62], constant error [30, 42], variable global error [30, 42], root mean square error [30], and maximal overshoot [49] was reported. In two studies, a mid-range task reporting on absolute [43, 69], constant, and variable global error was reported, and in three papers [48, 64, 65], no specification of the error measurement parameter was reported. All nine studies showed smaller joint positioning error for the healthy controls compared with the neck pain groups; the difference was statistically significant in five studies [27, 34, 47, 64].…”
Section: Resultsmentioning
confidence: 99%
“…This study presents some limitations. First, neck ROM was limited to 30°, that allowed us to avoid the strain of the neck passive system (joint capsules, facet joints, intervertebral disks and ligaments) and to improve input from the upper cervical proprioceptive system which is highly developed in the sub-occipital region upper neck (Dugailly et al, 2015) and which corresponds to the spinal muscles that provides dynamic stability during the first degrees of rotation (Panjabi, 1992). Second, only head-neck rotational movement was assessed but rotation seems to be a regular movement during daily activities, the assessment of other motion directions (e.g., flexion/extension) appears to have limited interest.…”
Section: Discussionmentioning
confidence: 99%
“…Various noninvasive three-dimensional motion capture systems are used in the field of cervical research in order to evaluate kinematic variables going beyond simple range of motion such as speed, acceleration and deceleration using electrogoniometers [16], ultrasound waves [17], optical-based systems [18,19] and inertial sensors [20] and so on. Nevertheless, their dimension, complexity, and cost make such systems often difficult to use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%